2000
DOI: 10.1073/pnas.97.16.9052
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB signal transduction pathway in aortic endothelial cells is primed for activation in regions predisposed to atherosclerotic lesion formation

Abstract: Atherosclerotic lesions form at distinct sites in the arterial tree, suggesting that hemodynamic forces influence the initiation of atherogenesis. If NF-B plays a role in atherogenesis, then the activation of this signal transduction pathway in arterial endothelium should show topographic variation. The expression of NF-B͞ IB components and NF-B activation was evaluated by specific antibody staining, en face confocal microscopy, and image analysis of endothelium in regions of mouse proximal aorta with high and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
430
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(460 citation statements)
references
References 37 publications
23
430
0
3
Order By: Relevance
“…Although some other studies have suggested a proatherogenic role of TNF␣ signaling, this role may depend on the cell type involved as well as the specific receptors and signaling pathways downstream of TNF␣. Thus, there seems to be abundant evidence for a proatherogenic role of TNF␣ signaling in endothelial cells (49,50). In contrast, TNF␣ signaling via NF-B in macrophages and smooth muscle cells may have antiatherogenic consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Although some other studies have suggested a proatherogenic role of TNF␣ signaling, this role may depend on the cell type involved as well as the specific receptors and signaling pathways downstream of TNF␣. Thus, there seems to be abundant evidence for a proatherogenic role of TNF␣ signaling in endothelial cells (49,50). In contrast, TNF␣ signaling via NF-B in macrophages and smooth muscle cells may have antiatherogenic consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of adenosine used in our studies are not uncommon physiologically (Traut, 1994). Because of the critical role of NF-kB in a wide variety of diseases including cardiovascular diseases, RA and nephritis (Albrecht et al, 1995;Miagkov et al, 1998;Zwacka et al, 1998;Li et al, 1999Li et al, , 2000Hajra et al, 2000), the present study provides us another potential means of downregulating the activation of this transcription factor.…”
Section: Adenosine Blocks Tnf-mediated Nf-jb Activation S Majumdar Anmentioning
confidence: 95%
“…Most of these agents induce the phosphorylation-dependent degradation of IkBa proteins, allowing active NF-kB to translocate to the nucleus where it regulates gene expression. The activation of NF-kB has been detected in various inflammatory diseases, including RA, septic shock, and myocardial ischemia (Miagkov et al, 1998;Zwacka et al, 1998;Li et al, 1999;Hajra et al, 2000), known to be affected by adenosine. Since the expression of most inflammatory cytokines (e.g., TNF), known to be modulated by adenosine, is also regulated by NF-kB activation (Albrecht et al, 1995), we postulate that adenosine mediates its effects through suppression of NF-kB.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in lesion prone areas of the circulation there is increased expression of p65 as well as I K␣ and I K␤ (30). Interestingly, NO ⅐ has been shown to inhibit NF B activation via at least two mechanisms.…”
Section: Discussionmentioning
confidence: 99%